Rubus dorcheae (Rosaceae), a new species from central Nepal - Rokaya, Maan B.; Subedi, Sajan (Phytotaxa, 2021)
Rubus dorcheae M.B. Rokaya & S. Subedi, a new Rubus L. species recorded from the subtropical forest in central Nepal is described and illustrated. Notes to distinguish it from related taxa are provided. It is closely related to R. kumaonensis N.P. Balakr. and R. rugosus Sm. but differs by having more height, both leaf surfaces green, upper surface more hairy than lower surface, leaf blade margins biserrate, sepal deltoid, tomentose on both sides, margin with 7–10 appendages, apex bifurcate or trifurcate, petals spathulate, and calyx, corolla and stamens persistent in fruit. The species is categorized as Not Evaluated based on the IUCN Red List categories and criteria.